Editorial - Martin van Bruinessen, (Kurdish Studies, 2016)
The travellers, diplomats, missionaries and academics who have written on the Kurds have always shown a remarkable fascination with the Yezidis. The great Ottoman traveller Evliya Çelebi, who in the mid-seventeenth century wrote so extensively on diverse aspects of Kurdish culture, social life and political organisation that he may well be called the first Kurdologist, was also one of the first to write some tantalising observations on customs and practices of the Yezidis he encountered. He also reports in some detail on two punitive campaigns mounted by Ottoman governors against the Yezidis of Sinjar, in one of which he played a minor role himself. Christian missionaries based in Kurdistan were drawn to the Yezidis as the major non-Muslim and non-Christian community and fascinated by what they understood of its elusive theology. Two of the founders of West European academic Kurdology, C. J. Edmonds and Roger Lescot, devoted some of their major work to the Yezidis, and most Kurdish experts have felt the need to pay due attention to the Yezidi religion. Several of the ideologists of Kurdish nationalism, finally, have elevated the Yezidis to the status of most authentic Kurds. For more has been written about the Yezidis and their religion than about the religious practices and institutions of the Muslim Kurds, reflecting a bias among both foreign academics and secular Kurdish nationalists.